Potential T cell epitopes of Mycobacterium tuberculosis that can instigate molecular mimicry against host: implications in autoimmune pathogenesis - Babu Chodisetti Sathi; Rai Pradeep K; Gowthaman Uthaman; Pahari Susanta; Agrewala Javed N (BMC Immunology, 2012)
Abstract Background Molecular mimicry between microbial antigens and host-proteins is one of the etiological enigmas for the occurrence of autoimmune diseases. T cells that recognize cross-reactive epitopes may trigger autoimmune reactions. Intriguingly, autoimmune diseases have been reported to be prevalent in tuberculosis endemic populations. Further, association of Mycobacterium tuberculosis (M. tuberculosis) has been implicated in different autoimmune diseases, including rheumatoid arthritis and multiple sclerosis. Although, in silico analyses have identified a number of M. tuberculosis specific vaccine candidates, the analysis on prospective cross-reactive epitopes, that may elicit autoimmune response, has not been yet attempted. Here, we have employed bioinformatics tools to determine T cell epitopes of homologous antigenic regions between M. tuberculosis and human proteomes. Results Employing bioinformatics tools, we have identified potentially cross-reactive T cell epitopes restricted to predominant class I and II alleles of human leukocyte antigens (HLA). These are similar to peptides of mycobacterial proteins and considerable numbers of them are promiscuous. Some of the identified antigens corroborated with established autoimmune diseases linked with mycobacterial infection. Conclusions The present study reveals many target proteins and their putative T cell epitopes that might have significant application in understanding the molecular basis of possible T cell autoimmune reactions during M. tuberculosis infections.